Health and Wellness Food Products : A Retailers' Perspective - Dr. Dilipkumar L. Boinwad,; Prof. Rajesh S. Shinde, (International Journal of Scientific Research in Science and Technology, 2024)
Health and wellness food products have emerged as a pivotal category within the food and beverage industry, driven by the growing consumer emphasis on a nutritive diet and a sustainable lifestyle. This marked shift towards health-conscious consumption patterns reflects a global movement towards preventive healthcare, where individuals are more invested in the nutritional quality and health benefits of their food choices. The increasing consumer focus on health and wellness has prompted a significant shift in the retail food industry. This paper explores the perspectives of retail stakeholders on wellness foods, examining how demographic factors such as age, gender, education, geographic location, and the roles within the retail industry influence decision-making processes related to the stocking and promotion of such products. Through a survey-based study with a diverse group of retail professionals, researcher analyzed trends in sales, marketing strategies, and consumer demand for wellness foods. Researcher also investigates the dynamics between different income levels and their impact on the opinions and actions of retail representatives. Researcher’s findings provide a comprehensive overview of the current market, highlighting the challenges retailers face and the opportunities they perceive in the realm of wellness foods. This research not only contributes valuable insights for academic understanding but also serves as a strategic guide for retailers looking to navigate the evolving landscape of health-oriented consumerism.
Keywords: Health and Wellness Products; Preventive Healthcare; Market Trends; Urban Consumption